Inhibition of Oxidative Stress and ALOX12 and NF-κB Pathways Contribute to the Protective Effect of Baicalein on Carbon Tetrachloride-Induced Acute Liver Injury - Chongshan Dai; Hui Li; Yang Wang; Shusheng Tang; Tony Velkov; Jianzhong Shen (Antioxidants, 2021)
This study investigates the protective effect of baicalein on carbon tetrachloride (CCl4)-induced acute liver injury and the underlying molecular mechanisms. Mice were orally administrated baicalein at 25 and 100 mg/kg/day for 7 consecutive days or ferrostatin-1 (Fer-1) at 10 mg/kg was i.p. injected in mice at 2 and 24 h prior to CCl4 injection or the vehicle. Our results showed that baicalein or Fer-1 supplementation significantly attenuated CCl4 exposure-induced elevations of serum alanine aminotransferase and aspartate aminotransferase, and malondialdehyde levels in the liver tissues and unregulated glutathione levels. Baicalein treatment inhibited the nuclear factor kappa-B (NF-κB) pathway, activated the erythroid 2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway in liver tissues, and markedly improved CCl4-induced apoptosis, inflammation and ferroptosis in liver tissues exposed with CCl4. In vitro, baicalein treatment improved CCl4 -induced decreases of cell viabilities and knockdown of Nrf2 and arachidonate 12-lipoxygenase (ALOX12) genes partly abolished the protective effect of baicalein on CCl4 -induced cytotoxicity in HepG2 cells. In conclusion, our results reveal that baicalein supplementation ameliorates CCl4-induced acute liver injury in mice by upregulating the antioxidant defense pathways and downregulating oxidative stress, apoptosis, inflammation and ferroptosis, which involved the activation of Nrf2 pathway and the inhibition of ALOX12 and NF-κB pathways.